ANALSIS KINERJA HOME INDUSTRY BATIK DI DESA PAPRINAN KECAMATAN BANYUMAS KABUPATEN BANYUMAS - Anisa Fatmawati; Tjahjani Murdijaningsih; Krisnhoe Sukma Danuta; Trias Tinton Handy Rahmawan (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The existence of micro, small and medium enterprises (MSMEs) plays an important role in the economy of a region or country, especially in Indonesia. Papringan village is one of the villages with potential for progress in the batik industry sector, where this village has assets of Banyumasan batik where most of the women in Papringan village have batik activities to fill their spare time, in order to help family income. , efficiency, BEP, and the level of welfare of the batik home industry business in Papringan Village, Banyumas District, Banyumas Regency. This study uses the analysis method of the micro approach formula, and KHL analysis. The results of this study indicate that the home business of the batik industry is in a favorable condition with an average net income of Rp. 759,011, and has been efficient with an R/C ratio > 1, which is 1.3. The average BEP in Units is 2 units and BEP in rupiah is Rp. 877,865, these results show the BEP value is smaller than the average number of productions of 18 units, and the average revenue is Rp. 347,121. while the welfare level of batik business actors is mostly not prosperous, this is indicated by the average per capita income of Rp. 957,595 which is still below the UMK Banyumas 2022.